Medical comorbidities in patients with chronic lymphocytic leukaemia treated with idelalisib: analysis of two large randomised clinical trials. (29th June 2020) - Gordon, Max J.; Huang, Julie; Chan, Rebecca J.; Bhargava, Pankaj; Danilov, Alexey V.
Summary: Comorbidities influence survival in patients with chronic lymphocytic leukaemia (CLL) treated with chemo‐immunotherapy or ibrutinib. While idelalisib has been studied in patients with comorbidities, their impact has not been investigated. We analysed 481 patients treated with idelalisib on two randomised trials (NCT01659021 and NCT01539512). Comorbidities were assessed using the Cumulative Illness Risk Scale (CIRS). Patients received idelalisib + anti‐CD20 (rituximab or ofatumumab; n = 284) or anti‐CD20 alone ( n = 197). The median age was 69 years. We found that comorbidities did not significantly affect outcomes of idelalisib therapy. The objective response rate (ORR) was 79·3% versus 85·8%, the median progression‐free survival (PFS) was 16·3 versus 19·1 months, and the median overall survival (OS) was 39·8 versus 49·8 months in patients treated with idelalisib who had a CIRS score of >6 versus ≤6, correspondingly. Treatment with idelalisib + anti‐CD20 was associated with superior PFS and ORR when compared to anti‐CD20 monotherapy in patients who had high comorbidities (CIRS score of >6) or at least one severe comorbidity (median PFS 16·3 vs. 6·9 months and 16·6 vs. 6·5 months; odds ratio 20·1 and 33·2; P < 0·0001). Thus, comorbidities do not portend inferior outcomes in patients with CLL treated with idelalisib in combination with anti‐CD20 therapy.